Rinofaringitis aguda en niños que acuden al servicio de consulta externa en el Subcentro de San Cayetano y su relación con la administracion de la vacuna contra la influenza durante el periodo mayo-octubre 2012. - Poma Vélez, David Francisco (2013)
This research deals with the relationship between acute nasopharyngitis and administration of influenza vaccine. This pathology, not being prevented by vaccination and other measures, may in infants, causing complications. So it is necessary to assess its scope, so that they can improve strategies in this activity. In this study, conducted in the San Cayetano SCS; involved parents, patients and health; failing to meet the overall objective: To determine the cases of acute nasopharyngitis in children attending outpatient service in the San Cayetano SCS, with the Administration of Influenza Vaccine, and specific. Based on the results, it was found: the most common age to purchase Acute nasopharyngitis is 1-4 years, especially girls (50.72%: 49.28%). Of the vaccinated a 32.69% had no adverse reactions; however, of those who had, the pain at the site of placement of the vaccine predominated. A 38.46% of cases showed reinfection. It can be concluded that vaccination campaigns are effective, with appropriate biological. However, lack socialization, to dispel myths about vaccination, which make some people continue to resist this. Keywords: Acute nasopharyngitis, influenza vaccine, children, Vaccination.